La fête de Pâques : transgressions et instrumentalisations au sein des pratiques touristiques. Le cas de Maramureş en Roumanie - Sonia Catrina (Études Caribéennes)
The purpose of this paper is to analyze the way in which the guesthouse owners from Maramureş carry out a social and symbolic construction of their identity in the presence of the tourists during the season of fasting, reflection and preparation before the celebration of Easter, during this religious holiday and the days after that. Starting from a socio-anthropological description of the “ingredients” of this religious holiday we aim at identifying its transgressions and their meanings in the context of the rural family-type tourism. We try to understand the “how” and the “why” of the logics which are behind the instrumentalisation of certain symbols of this religious holiday in the private sphere of identification. We assume that the disobedience to certain ancestral practices associated with this religious holiday answers the guesthouse owners’ tourism marketing needs. Behind the study of the mechanisms of “putting on display” items of collective identification selected by the guesthouse owners, it is the question of identity which is the heart of our reflection.